Eksplorasi Pengalaman PAI Melalui Model Flipped Classroom: Studi Kasus Pada Siswa SD Eropa di Surabaya - Moh Subhan; Misbakhus Surur (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to explore the effectiveness of the Flipped Classroom Model in Islamic Religious Education (PAI) learning at European Elementary School in Surabaya. This model offers an innovative approach by providing instructional materials before face-to-face sessions, allowing classroom time to be utilized for discussions and concept applications. The study employs a qualitative approach using in-depth interviews, participatory observations, and document analysis. The findings indicate that the Flipped Classroom Model enhances students' understanding of Islamic Religious Education by enabling them to learn independently at their own pace. This approach also helps bridge the cultural and religious background differences among students, both Muslim and non-Muslim, in understanding Islamic values contextually. However, limited access to technology remains a major challenge in implementing this method. Therefore, technological infrastructure support and teacher training are crucial factors in the successful implementation of the Flipped Classroom Model in a multicultural educational environment.